Data Management Technologies and Applications : 5th International Conference, DATA 2016, Colmar, France, July 24-26, 2016, Revised Selected Papers /: 5th International Conference, DATA 2016, Colmar, France, July 24-26, 2016, Revised Selected Papers. (2017) - Unknown
No abstract available